Harmonizing Math and Culture: Exploring Ethnomathematics in Malay Culture through Children's Storybooks - Cici Oktaviani; Herwin Herwin; Muh Rifqienur Adiwardana; Zeva Adi Fianto; Shakila Che Dahlan (Journal of Innovation in Educational and Cultural Research, 2024)
The application of mathematics has always been related to everyday life. This study aims to describe the relationship between mathematics and Malay culture integrated with the children's storybook “Asyiknya bermain galah panjang; Pembuatan Jalur; Matematika di Rumah Adat Riau Selaso Jatuh Kembar”. This research is qualitative descriptive research, with data collection techniques using literature studies from 3 children's story books from the elementary school teacher education study program. The data analysis technique carried out is content analysis. The results show that children's storybooks in this study presented cultural content in several aspects, such as clothing, language, and activities. The mathematical content linked in this children's storybook is between the traditional game of long poles that form a flat square and rectangular wake pattern. The process of creating paths related to standard and non-standard measurement materials. Then, the Selaso Fall Twin House's architecture can be associated with the mathematical material: flat and angular shapes. The interconnectedness between maths and culture in these children's storybooks can provide readers with valuable insights, especially children, into how maths is a relevant part of their daily lives and cultures.